scully, an essential gene of Drosophila, is homologous to mammalian mitochondrial type II L-3-hydroxyacyl-CoA dehydrogenase/amyloid-beta peptide-binding protein. - Torroja, L.; Ortuno-Sahagun, D.; Ferrus, A.; Hammerle, B.; Barbas, J.A. (Journal of Cell Biology, 1998)
The characterization of scully, an essential gene of Drosophila with phenocritical phases at embryonic and pupal stages, shows its extensive homology with vertebrate type II L-3-hydroxyacyl-CoA dehydrogenase/ERAB. Genomic rescue demonstrates that four different lethal mutations are scu alleles, the molecular nature of which has been established. One of them, scu3127, generates a nonfunctional truncated product. scu4058 also produces a truncated protein, but it contains most of the known functional domains of the enzyme. The other two mutations, scu174 and scuS152, correspond to single amino acid changes. The expression of scully mRNA is general to many tissues including the CNS; however, it is highest in both embryonic gonadal primordia and mature ovaries and testes. Consistent with this pattern, the phenotypic analysis suggests a role for scully in germ line formation: mutant testis are reduced in size and devoid of maturing sperm, and mutant ovarioles are not able to produce viable eggs. Ultrastructural analysis of mutant spermatocytes reveals the presence of cytoplasmic lipid inclusions and scarce mitochondria. In addition, mutant photoreceptors contain morphologically aberrant mitochondria and large multilayered accumulations of membranous material. Some of these phenotypes are very similar to those present in human pathologies caused by beta-oxidation disorders.